Splitting the e-Abacus Diagram in the Partition Theory - Mohammed, Hanan Salim; Abdul-Razaq, Nadia Adnan (Iraqi Journal of Science, 2021)
In the partition theory, there is more then one form of representation of dedication, most notably the Abacus diagram, which gives an accurate and specific description. In the year 2019, Mahmood and Mahmood presented the idea of merging more than two plans, and then the following question was raised: Is the process of separating any somewhat large diagram into smaller schemes possible? The general formula to split e-abacus diagram into two or more equal or unequal parts was achieved in this study now.